Game Based Learning Berbantuan Media Board Game Klaster untuk Meningkatkan Kemampuan Literasi Siswa - Diana, Husnud (Jurnal Didaktika Pendidikan Dasar, 2022)
This classroom action research aims to improve students' literacy skills through the application of game-based learning models assisted by cluster board game media (invertebrate classification cards). This research was conducted in 2 cycles, and each cycle consisted of stages of planning, action, observation, and reflection. The study used qualitative and quantitative data. Qualitative data were obtained through observing the process/activity of students' literacy during learning using a game-based learning model assisted by Cluster board game media. Quantitative data was obtained through a student's literacy ability test, namely the student's ability to solve problems involving higher order thinking skills (HOTS). The results showed that there was an increase in literacy processes/activities and literacy skills involving students' higher-order thinking skills (HOTS questions) in learning invertebrate classification materials.